Green‐solvent Processable Dopant‐free Hole Transporting Materials for Inverted Perovskite Solar Cells. Issue 11 (6th February 2023) - Yu, XinYu; Gao, Danpeng; Li, Zhen; Sun, Xianglang; Li, Bo; Zhu, Zonglong; Li, Zhong'an
Abstract: The commercialization of perovskite solar cells (PVSCs) urgently requires the development of green‐solvent processable dopant‐free hole transporting materials (HTMs). However, strong intermolecular interactions that ensure high hole mobility always compromise the solubility and film‐forming ability in green solvents. Herein, we show a simple but effective design strategy to solve this trade‐off, that is, constructing star‐shaped D‐A‐D structure. The resulting HTMs (BTP1‐2) can be processed by green solvent of 2‐methylanisole (2MA), a kind of food additive, and show high hole mobility and multiple defect passivation effects. An impressive efficiency of 24.34 % has been achieved for 2MA‐processed BTP1 based inverted PVSCs, the highest value for green‐solvent processable HTMs so far. Moreover, it is manifested that the charge separation of D‐A type HTMs at the photoinduced excited state can help to passivate the defects of perovskites, indicating a new HTM design insight. Abstract : Star‐shaped donor‐acceptor‐donor structure with 3, 5‐dicarbonitrile pyridine core has been developed as an efficient design strategy towards high performance green‐solvent processable dopant‐free hole transporting materials (HTMs). The resulting BTP1 HTM processed by the green solvent 2‐methylanisole, a kind of food additive, shows an impressive efficiency of 24.34 % based on inverted perovskite solar cells.